Kehidupan Sosial Ekonomi Nelayan Batang Arau Kecamatan Padang Selatan Kota Padang (2014-2020) - Revi Febriani; Rusdi Rusdi (Jurusan Sejarah FIS UNP, 2023)
ABSTRACT This study discusses the socio-economic life of fishermen in Batang Arau, South Padang District, Padang City (1990-2020). This research is based on the problem of changes in income that occur in Batang Arau fishermen due to assistance provided by the government. The purpose of this study is to see how the socio-economic life of fishermen in Batang Arau has been since 1990 with government assistance and the impact on fishermen and in 2020 the decline in fishermen's income due to Covid-19. The research method used in this study is the historical method. Which consists of four stages, namely: heuristics, source criticism, interpretation, and historiography. From the results of this study it was found that the socio-economic life conditions of fishermen were still relatively low due to several things including: (1) low level of education. (2) Going to sea depends on natural conditions or the transition season. (3) Traditional fishing gear. (4) fishermen's lack of knowledge in managing the marketing of their marine products. And to help the fishermen's economy, the government through the Maritime Affairs and Fisheries Council distributed assistance in the form of fishing gear, boats and engines. And with this assistance, it provides sufficient impact and results to help fishermen's daily needs and improve the welfare of fishermen's families. Keyword: Fisherman, Socio-Economic, Government ABSTRAK Penelitian ini membahas tentang kehidupan sosial ekonomi nelayan Batang Arau Kecamatan Padang Selatan Kota Padang (1990-2020). Penelitian ini berlatarkan masalah perubahan pendapatan yang terjadi pada nelayan Batang Arau akibat bantuan yang diberikan pemerintah. Tujuan dari penelitian ini untuk melihat bagaimana kehidupan sosial ekonomi nelayan di Batang Arau sejak tahun 1990 dengan adanya bantuan pemerintah dan dampaknya bagi nelayan dan tahun 2020 merosotnya pendapatan nelayan akibat Covid-19. Metode penelitian yang digunakan dalam penelitian ini adalah metode sejarah. Yang terdiri dari empat tahap yaitu: heuristik, kritik sumber, interpretasi, dan historiografi. Dari hasil penelitian ini didapatkan bahwa kondisi kehidupan sosial ekonomi nelayan masih tergolong rendah disebabkan oleh beberapa hal diantaranya: (1) tingkat pendidikan yang rendah. (2) Melaut tergantung dengan kondisi alam atau musim pancaroba. (3) Alat tangkap yang masih tradisional. (4) kurangnya pengetahuan nelayan dalam mengelola pemasaran hasil lautnya. Dan untuk membantu perekonomian nelayan, pemerintah melalui Dewan Kelautan dan Perikanan menyalurkan bantuan berupa pemberian alat tangkap, perahu dan mesin. Dan dengan bantuan tersebut memberikan dampak dan hasil yang cukup untuk membantu kebutuhan sehari-hari nelayan dan menyejahterakan kehidupan keluarga nelayan. Kata Kunci: Nelayan, Sosial-Ekonomi, Pemerintah